Life history aspects of two species of the Squalus genus in the Eastern Ionian Sea. (9th January 2017) - Anastasopoulou, Aikaterini; Mytilineou, Chryssi; Makantasi, Panayiota; Smith, Christopher J.; Kavadas, Stefanos; Lefkaditou, Eugenia; Papadopoulou, Konstantia N.
Abstract : Data on life history aspects of two species of Squalus genus were collated from five different studies carried out in the Eastern Ionian Sea from 1995 to 2014. Data were collected from 948 longnose spurdogs Squalus blainville (Risso, 1827) and 65 spiny dogfish Squalus acanthias Linnaeus, 1758 caught by trawl and longlines. The mean length of both species increased with depth. Sexual segregation was observed for S. blainville, whereas a segregation of immature and mature individuals was detected for S. acanthias . The length–weight relationship for S. blainville indicated positive allometry ( b > 3) for both sexes, whereas a negative allometry ( b < 3) was found for S. acanthias for the combined sexes. The sex ratio of both species was in favour of males. For S. blainville, the gonadosomatic and hepatosomatic indices differed significantly between sexes but not between seasons with the maturity data supporting the hypothesis of continuous reproduction throughout the year. Length at first maturity (L50 ) for female and male S. blainville was 603 and 413 mm respectively. For S. acanthias, males collected in autumn had finished their spawning activity; the single specimen caught in summer was reproductively active. Females, caught only in summer, were all gravid. Prey identified in the stomachs of S. blainville belonged to three major groups: fish, cephalopods and shrimps. Other groups such as echinoderms and ascidians were also found. Identified prey in the stomachs of S. acanthias belonged to two main groups, fish and cephalopods, although other groups (including echinoderms and polychaetes) were also present.